The impact of the COVID-19 pandemic on oral anticoagulation adherence in patients with atrial fibrillation managed in primary care: Results from the PRIME Registry - Omer Atac; Volkan Aydin; Lars E. Peterson; Teresa M. Waters (PLoS ONE, 2026)
Background Oral anticoagulants (OACs) are critical for preventing stroke in patients with atrial fibrillation (AF), yet adherence and persistence remain suboptimal, especially in primary care settings. The COVID-19 pandemic introduced new barriers to care that may have further disrupted medication use. This study aimed to examine the impact of the COVID-19 pandemic on OAC adherence and persistence among patients with nonvalvular AF managed in primary care practices. Methods In this retrospective cohort study, we used clinical records from the American Board of Family Medicine’s (ABFM) PRIME Registry, for March 2017 through March 2023. We included 3,010 patients with documented AF and at least two OAC prescriptions prior to baseline. Persistence was assessed annually using a treatment anniversary method, and adherence was measured using the proportion of days covered (PDC), analyzed among persistent patients only. Interrupted time series and multivariable logistic regression models evaluated changes in quarterly persistence and factors associated with persistence and good adherence. Results Persistence declined sharply during the pandemic from 49.9% in 2018–2019 to 8.2% in the pandemic year-1. Adherence also dropped, with >95% PDC decreasing from 46.0% pre-pandemic to 17.7% in the pandemic year-2. Interrupted time series analysis showed a significant immediate drop in persistence. Compared to warfarin, NOAC use was associated with lower persistence in the pre-pandemic period, but higher persistence by the second year of the pandemic. Conclusions The COVID-19 pandemic was associated with sustained declines in OAC adherence and persistence among AF patients in primary care. Targeted interventions including telemedicine, home-based care, and attention to high-risk subgroups are essential to maintain continuity of care and improve adherence during public health crises.